Emotional dependency: a systematic review of literature - Denise Catricala Bution; Amanda Muglia Wechsler (Estudos Interdisciplinares em Psicologia, 2016)
Emotional Dependency is a disorder characterized by addictive behaviors in romantic relationships. However, there is still controversy about whether this dependency should be considered pathological, as well as its appropriate denomination and the symptoms that would define it. This paper presents a systematic evaluation of the literature on emotional dependency, reviewing all the indexed articles in Scielo, CAPES, and Scholar Google databases, published between 2000 and 2014. After careful analysis, 20 studies were selected. The results show that emotional dependency is defined as an addictive disorder, in which the individual needs another to maintain his emotional balance. Its etiology is related to the development of attachment during childhood, in addition to cultural and phylogenetic factors. The indicated treatments are individual therapy, group therapy, support groups and self-help books. We point out some inconsistencies among the studies, showing the need for more research to elucidate these questions.